The effect of organic cation dynamics on the optical properties in (PEA)₂(MA)[Pb₂I₇] perovskite dimorphs - Lekina, Yulia (2023)
Two-dimensional (2D) phenylethyl ammonium (PEA+)-methyl ammonium (MA+) lead iodide ((PEA)2(MA)[Pb2I7]) hybrid perovskite exists as temperature-dependent dimorphs exhibiting an ill-defined phase transition occurring over the 150–200 K range. Raman scattering, photoluminescence, optical absorbance and solid state MAS NMR spectroscopic methods are employed to investigate the structural complexity, disorder and structure/function of this system. The Raman and 1H MAS NMR data indicate that the lower bounds of the phase transition at ∼150 K are characterised by attenuated rotational modes and slower motional dynamics throughout the disordered MA+ organic sublattice, inducing a strengthening of the MA+⋯I hydrogen bonds and a 5 meV increase in the excitonic and photoluminescence energies. It is evident that different recombination mechanisms are dominant for the room temperature and low temperature phases reflecting the importance of MA+ dynamics in the optical properties of the material. Single crystal X-ray studies are unable to position the organic cations within the Pb2I7 framework; however, 1H/13C MAS NMR measurements describe elements of local structural disorder based on conformational isomerism within the PEA+ sublattice. Concomitant I− and Pb2+ migration and [Pb2I7]3− framework defects create stacking disorder, dislocations and dispersed octahedral tilting leading to additional disorder and distributed MA+ and PEA+ cation dynamics.